A hierarchical fuzzy comprehensive evaluation algorithm for running states of an electromechanical system. (1st April 2021) - Wang, Fuzhong; Han, Sumin; Li, Yuanyuan; Zhou, Meng
Abstract : A fuzzy hierarchical comprehensive evaluation algorithm including fuzzy matrix and comprehensive evaluation matrix calculation thought is proposed to accurately evaluate the running state of an electromechanical system. The analytic hierarchy process is included in the algorithm, which calculates the state of each subsystem from top to bottom and the states are used as the evaluation factor of the upper system. The idea of degradation degrees is introduced to standardize the indicators. The paper carried out the simulation experiment for the electromechanical system with a model number of JKMD-4 × 4(Z). The experimental results show that the established state evaluation model can accurately judge the operation state of the system with not too much data.